Advancing the science of distress screening and management in cancer care. (2020) - Donovan, Kristine A.; Grassi, Luigi; Deshields, Teresa L.; Corbett, Cheyenne; Riba, Michelle B.
Abstract: Given the high prevalence (30–35%) of psychosocial and psychiatric morbidity amongst cancer patients in any phase of the disease trajectory, screening for emotional problems and disorders has become mandatory in oncology. As a process, screening begins at the entry to the cancer care system and continues at clinically meaningful times, periodically during active cancer care, or when clinically indicated. The goal is to facilitate proper referral to psychosocial oncology specialists for more specific assessment and care, as well as treatment and evaluation of the response, according to the implementation of distress management guidelines. In this editorial, we will provide a non-exhaustive overview of relevant protocols, with particular reference to the National Comprehensive Cancer Network (NCCN) Distress Management in Oncology Guidelines, and review the challenges and the problems in implementing screening, and the assessment and management of psychosocial and psychiatric problems in cancer centres and community care.